2013
DOI: 10.1155/2013/937487
|View full text |Cite
|
Sign up to set email alerts
|

Limited Mouth Opening Secondary to Diffuse Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a relatively rare condition with an immunologically mediated pathogenesis. For reasons that are not clearly understood, dense collagen is deposited in the connective tissues of the body in extraordinary amounts. Although its dramatic effects are seen in association with the skin, the disease is often quite serious with visceral organ involvement. We describe a case of limited mouth opening secondary to diffuse SSc, improvement in mouth opening with passive jaw stretch exercises, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Reports of surgical interventions to enlarge the oral orifice such as bilateral commissurotomy or commissuroplasty have been described but represent very invasive procedures (Johns et al , ; Mehra et al , ; TerzIoğlu et al , ; Koymen et al , ). Active (placing the thumbs in opposite corners of the mouth and pulling outwards) or passive (using tongue depressors inserted between the posterior teeth) mouth‐stretching exercises, facial grimacing, connective tissue massage, Kabat's techniques, or kinesitherapy can be proposed as an initial non‐surgical alternative to improve mouth opening, oral functions, and skin elasticity (Pizzo et al , ; Maddali‐Bongi et al , ; Wada and Ram, ). Encouraging SSc patient to perform exercises since the earliest phases of the disease will help to limit the extension of skin fibrosis.…”
Section: Oral Managementmentioning
confidence: 99%
“…Reports of surgical interventions to enlarge the oral orifice such as bilateral commissurotomy or commissuroplasty have been described but represent very invasive procedures (Johns et al , ; Mehra et al , ; TerzIoğlu et al , ; Koymen et al , ). Active (placing the thumbs in opposite corners of the mouth and pulling outwards) or passive (using tongue depressors inserted between the posterior teeth) mouth‐stretching exercises, facial grimacing, connective tissue massage, Kabat's techniques, or kinesitherapy can be proposed as an initial non‐surgical alternative to improve mouth opening, oral functions, and skin elasticity (Pizzo et al , ; Maddali‐Bongi et al , ; Wada and Ram, ). Encouraging SSc patient to perform exercises since the earliest phases of the disease will help to limit the extension of skin fibrosis.…”
Section: Oral Managementmentioning
confidence: 99%
“…It is indicated that patients with SS have regular dental appointments [8]. The knowledge that the patient has Systemic scleroderma (SS) disease makes the pediatric dentist to act accordingly, as for example with the difficulty of mouth opening to make molds, because patients with SS have difficulty in stretching and keeping their mouths open which can make treatments extremely difficult [9].…”
Section: Discussionmentioning
confidence: 99%
“…Some publications have shown structural and functional involvement of the stomatognathic system [5][6][7][8][9][10] , justifying the importance of including Speech, Language and Hearing Sciences in Rheumatology clinics.…”
Section: Discussionmentioning
confidence: 99%
“…In researches conducted by rheumatologists and dentists, were cited a few manifestations of Speech, Language and Hearing Sciences studies, including microstomia, xerostomia, loss of gengival mucosa 5 , laryngeal impairment, oropharyngeal dysphagia 6,7 , difficulty in chewing, tongue rigidity, changes in the production of bilabial sounds due to the limitation of mandibular movements and vocal changes [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%